2022
DOI: 10.1007/s00216-022-04189-y
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid and steroid analysis in infant and adult nails by LC–MS/MS

Abstract: A common method to quantify chronic stress is the analysis of stress markers in keratinized matrices such as hair or nail. In this study, we aimed to validate a sensitive liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for the combined quantification of steroid hormones and endocannabinoids (eCBs) in the keratinized matrix nail. Furthermore, we aimed to investigate the suitability of the nail matrix for the detection of these stress markers in a pilot study. An LC–MS/MS method was used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…It is not surprising that the highest P4 concentrations were observed at the second postpubertal sampling time, as both biological specimens had been exposed to accumulating circulating hormones for a longer duration. Compared to P4 concentrations in claws from calves and pregnant cows [ 25 ], P4 concentrations in nails in our study were very similar to the ~20 pg/mg reported for calves and fell within the wide range of 14.32–103.66 pg/mg reported for pregnant cows, but were more than twofold higher than the range of 0.7–12.8 pg/mg reported in women using a different laboratory technique [ 39 ]. Because the laboratory technique employed by Comin et al [ 25 ] was similar to ours, it can be assumed that, although species-related differences must be considered, sexual steroid concentrations in nails/claws are strongly influenced by the method of analysis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It is not surprising that the highest P4 concentrations were observed at the second postpubertal sampling time, as both biological specimens had been exposed to accumulating circulating hormones for a longer duration. Compared to P4 concentrations in claws from calves and pregnant cows [ 25 ], P4 concentrations in nails in our study were very similar to the ~20 pg/mg reported for calves and fell within the wide range of 14.32–103.66 pg/mg reported for pregnant cows, but were more than twofold higher than the range of 0.7–12.8 pg/mg reported in women using a different laboratory technique [ 39 ]. Because the laboratory technique employed by Comin et al [ 25 ] was similar to ours, it can be assumed that, although species-related differences must be considered, sexual steroid concentrations in nails/claws are strongly influenced by the method of analysis.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, the similar profiles of T concentrations in both hair and nails suggest that both biological specimens can serve as alternatives to assess changes in T concentration in dogs. The concentrations of E2 and P4 in males did not exhibit significant changes over the study period in either biological specimen, with similar profiles and low concentrations, albeit about tenfold higher than the P4 concentrations reported in nails in men (1.0–2.1 pg/mg) [ 39 ].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Drugs and metabolites can be analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) from biological matrices, including blood ( 15 ), hair ( 16 ), and nails ( 17 ). In forensic toxicology, retrospective quantification of chemicals in hair samples has gained widespread acceptance.…”
Section: Introductionmentioning
confidence: 99%